Effect of grazing legume or grass forages with or without corn supplementation on animal performance and meat quality of forage-finished beef - Wright, Asher (2013)
Angus x Hereford steers (n = 32) were used in a 2-yr study to examine forage type (legume: alfalfa and soybeans, LG vs. grass: tall fescue and sudangrass, GR) and individual daily corn supplementation (0, NS vs. 0.75% BW, CS) on animal performance and carcass quality. Steers were finished to an equal time endpoint (105 d) and slaughtered. Steaks (2.5 cm thick) from LM were obtained for proximate analysis and tenderness after different postmortem aging times (2, 4, 7, 14, 28 d). Data were analyzed in a mixed model using a 2x2 factorial arrangement of treatments. Steer was the experimental unit and year included as a random effect. Corn supplementation (CS) increased (P < 0.05) average daily gain (ADG), hot carcass weight (HCW), dressing percentage (DP) and tended (P < 0.06) to increase fat thickness at the 12th rib (FT). CS also increased (P < 0.05) yield grade (YG) and tended to increase (P < 0.07) quality grade (QG). In terms of forage, LG increased (P < 0.05) DP and HCW, with a tendency to increase ADG (P < 0.06). CS resulted in lower (P < 0.05) concentrations of CLA c9t11 and n-3 FA in LM. Steers receiving CS had a higher (P < 0.05) n-6:n-3 ratio (3.1 vs. 2.4), but both are lower than the 4:1 ratio recommend by health officials. Steers on GR had higher (P < 0.05) concentrations of saturated FA in the LM due to increased (P < 0.05) stearic (C18:0) acid percentages. Longissimus muscle calcium content was higher (P < 0.05) for LG than GR. Alpha-tocopherol and beta-carotene were altered (P < 0.05) by forage-type and corn supplementation. Tenderness was only affected (P < 0.05) by postmortem aging. Grazing legumes during finishing improves HCW and DP, and tends to improve ADG. Corn grain supplementation to grazing steers improved animal performance while not negatively impacting the nutritional qualities of the meat.